2020
DOI: 10.3892/etm.2020.9320
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of NAFLD occurrence in prediabetes patients

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a component of metabolic syndrome that significantly increases the cardiovascular risk of patients with glucose metabolism alterations. This study identified the prevalence of NAFLD, predictors of NAFLD and explored the link between insulin sensitivity, insulin resistance and leptinemia in 143 patients registered with prediabetes. Abdominal ultrasound was performed, and fasting insulin, postprandial insulin, leptin levels, common clinical/biochemical determinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…We converted the eGFR into a categorical variable according to the quartile and calculated the P for the trend to test the results of the eGFR as the continuous variable and explore the possibility of non-linearity. As the risk of NAFLD was obviously increased in patients with diabetes mellitus ( 7 ), IFG ( 48 ), HTG ( 49 ), CKD ( 28 ), and elevated ALT ( 50 ). Therefore, when exploring the association between eGFR and incident NAFLD in other sensitivity analyses, we excluded participants with FPG > 6.1 mmol/L, TG ≥ 1.7 mmol/L, eGFR < 60 mL/min⋅1.73 m 2 , or ALT > 40 U/L.…”
Section: Methodsmentioning
confidence: 99%
“…We converted the eGFR into a categorical variable according to the quartile and calculated the P for the trend to test the results of the eGFR as the continuous variable and explore the possibility of non-linearity. As the risk of NAFLD was obviously increased in patients with diabetes mellitus ( 7 ), IFG ( 48 ), HTG ( 49 ), CKD ( 28 ), and elevated ALT ( 50 ). Therefore, when exploring the association between eGFR and incident NAFLD in other sensitivity analyses, we excluded participants with FPG > 6.1 mmol/L, TG ≥ 1.7 mmol/L, eGFR < 60 mL/min⋅1.73 m 2 , or ALT > 40 U/L.…”
Section: Methodsmentioning
confidence: 99%
“…The administration of Sinapine reduced the ratio of Firmicutes to Bacteroidetes and increased the abundance of Lactobacillaceae, Akkermansiaceae , and Blautia . Moreover, Sinapine stimulated G protein-coupled upregulation 43 (GPR43) of short-chain fatty acid (SCFA) in order to suppress the causes of inflammation [ 202 , 203 , 204 ]. A recent research study also found that PPs decreased microbiota dysbiosis by scavenging intestinal reactive oxygen species (ROS) through gut metabolism.…”
Section: The Interaction Between Dietary Polyphenols (Prebiotics) mentioning
confidence: 99%
“…Oxidative stress induced by nocturnal intermittent hypoxia is reversible with CPAP therapy, leading to a significant reduction in leptin level (known as satiety hormone) and insulin resistance, respectively [ 154 ]. Observational studies suggest that CPAP might also improve daytime symptoms, quality of life, and the evolution of NAFLD [ 155 ], by decreasing liver enzymes [ 156 , 157 ].…”
Section: Management Of Sleep Disorders In Patients With Chronic LImentioning
confidence: 99%